2023
DOI: 10.2196/39965
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Shared Decision-Making Within Internet Hospitals in China Based on Patients’ Needs: Feasibility Study and Content Analysis

Abstract: Background Internet hospitals are developing rapidly in China, and their convenient and efficient medical services are being increasingly recognized by patients. Many hospitals have set up their own internet hospitals to provide web-based medical services. Tianjin Medical University General Hospital has established a multidisciplinary and comprehensive internet hospital to provide diversified medical services according to the needs of patients. A way to further improve web-based medical services is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…As of June 2023, there have been more than 3000 internet hospitals in China carrying out internet diagnosis and treatment services for more than 25.9 million people, and the scale of internet hospitals has increased by about 1300 compared with the end of 2021 [ 5 ]. Yu et al [ 6 ] confirmed the feasibility of implementing shared decision-making between doctors and patients in the diagnosis and treatment services of internet hospitals by analyzing the characteristics and medical needs of patients at the Tianjin Medical University General Hospital Internet Hospital, providing a new approach to enhancing patients’ medical experience. The organization can rely on the medical institution entity to establish an internet hospital to provide patients with safe and appropriate medical services via the internet [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As of June 2023, there have been more than 3000 internet hospitals in China carrying out internet diagnosis and treatment services for more than 25.9 million people, and the scale of internet hospitals has increased by about 1300 compared with the end of 2021 [ 5 ]. Yu et al [ 6 ] confirmed the feasibility of implementing shared decision-making between doctors and patients in the diagnosis and treatment services of internet hospitals by analyzing the characteristics and medical needs of patients at the Tianjin Medical University General Hospital Internet Hospital, providing a new approach to enhancing patients’ medical experience. The organization can rely on the medical institution entity to establish an internet hospital to provide patients with safe and appropriate medical services via the internet [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While greatly improving clinical diagnosis and treatment efficiency, they also provide significant satisfaction of patients 6 . At the same time, influenced by various factors, especially the increasing demand for patient diagnosis and treatment of pulmonary nodules, the continuous improvement of online diagnosis and treatment functions and the continuous expansion of service scope have become research focuses 7 . This article reviews the application and research progress of online diagnosis and treatment on the Internet in patients with pulmonary nodules in thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%